ACCELERATION IN STATE-OF-THE-ART ASR APPLIED TO A VIETNAMESE TRANSCRIPTION SYSTEM - Pham, Nhut Minh; Quân, Vũ Hải (Journal of Computer Science and Cybernetics, 2019)
This paper presents the adoption of state-of-the-art ASR techniques into Vietnamese. To better assess these techniques, speech corpora in the research community are assembled, and expanded, making a unified evaluation material under the name VN-Corpus. On this corpus, three ASR systems are built using the conventional HMM-GMM recipe, SGMM, and DNN respectively. Experimental results crown DNN with the overall WER of 12.1%. In the best case, DNN even cut down to 9.7% error rate.